2016
DOI: 10.1016/j.ejso.2016.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Current and future role of circulating tumor cells in patients with epithelial ovarian cancer

Abstract: Circulating tumor cells (CTCs) are viable tumor cells that are released into the circulatory system. CTCs have shown a prognostic value in numerous solid tumors. CTC research in epithelial ovarian carcinoma (EOC) has attracted only little attention. Since the primary route of metastasis in EOC is considered to be direct peritoneal spread in the abdominal cavity and distant metastases only occur in one third of the patients, it was thought that there is not enough shedding of tumor cells in the circulation. Nev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 69 publications
2
33
0
Order By: Relevance
“…Different detection methods were used, mainly based on immunocytochemistry (microscopic detection or the FDA-approved CellSearch ® system), RT-PCR (AdnaTest, QIAGEN, Hilden, Germany), and RT-qPCR for the quantification of CTCs levels [20,21]. The time point of blood collection also differed, however, in the majority of studies the peripheral blood samples were obtained before surgical removal of the tumor.…”
Section: Circulating Tumor Cells (Ctcs)mentioning
confidence: 99%
“…Different detection methods were used, mainly based on immunocytochemistry (microscopic detection or the FDA-approved CellSearch ® system), RT-PCR (AdnaTest, QIAGEN, Hilden, Germany), and RT-qPCR for the quantification of CTCs levels [20,21]. The time point of blood collection also differed, however, in the majority of studies the peripheral blood samples were obtained before surgical removal of the tumor.…”
Section: Circulating Tumor Cells (Ctcs)mentioning
confidence: 99%
“…Moreover, CTC analysis enables the detection of multiple mutations within a single cell, which contributes to an improved understanding of tumor heterogeneity and clonal evolution to establish a potential connection between mutational status and pathway activation by combining CTC genomics and transcriptomics [37]. However, the limitations include the lack of large-scale studies with standardized approaches to enrich and detect CTCs [38]. Most of the studies on ovarian CTCs using the FDA-approved CellSearch system reported negative results due to its comparatively low accuracy in CTC detection and the limited availability of patients with ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CTC analysis enables the detection of multiple mutations within a single cell which contributes to the understanding of tumor heterogeneity and clonal evolution, and this might establish a potential connection between mutational status and pathway activation by combining the genomics and transcriptomics of CTCs [23]. However, some limitations have to be overcome such as the lack of large scale studies with standardized approaches to enrich and detect CTCs [24].…”
Section: Discussionmentioning
confidence: 99%